The Role of Parents in Motvating Students to Learn English - Bambang Purwanto, Muhammad; Despita, Despita; Agustin, Ariya (Foreign Language Instruction Probe, 2023)
The purpose of this research is to find out how parents can motivate their children to learn English. This is referred to as "case study research." This research was conducted in the Ganesha Course tutoring class with five students and five parents as subjects. The data collection method used a learning motivation scale and interviews. The data analysis technique used descriptive and qualitative data analysis. Subject One demonstrated high learning motivation, and the role of parents was important in motivating children to learn English. Subject two has low motivation to learn; the role of parents is high in motivating students to learn English. Subject three has medium learning motivation and a strong parental role in motivating children to learn English. Subject four has a high motivation to learn, and the role of parents is important in motivating the learning of English. Subject five has low learning motivation; the role of their parents is to motivate her. As a result, it was determined that the role of parents in motivating learning subjects 1, 2, 3, 4 and our five low-level subjects was significant